Pasundan Delivery Services (PT. Wahana Bumi Raya) Business Strategy Formulation and Implementation to Create Sustain Future Competition - Haryanto, Iman; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2012)
Pasundan Delivery Services (PDS) is the delivery services provider using motorcycle provide solutions for visitors and Bandung citizens to effective and efficient their valuable time, run its costumer order through smartphone and social media, lucrative demand leads PDS to formulate its strategy to reach more costumers among existing competitors to win the competition in and as the leader the future. Formulation of strategic management involving small team discussion group as the management of PT. WBR, observations and employee sharing during evaluation. The methodology based on the strategic management framework. scanning the external environment and internal organization, this phase will identify possible opportunities and threats and its internal environment for strengths and weaknesses. The result of business strategy formulation, growth strategy for corporate level strategy and for business level strategy result on 2 choices of strategy selection, competitive and cooperative, consider its two major services, dine-in services currently faced barrier on reach higher number of costumers handling due to its limitation order process using smartphone device, migration into hotline costumer care is the best selection plan, cargo and document delivery services to deliver the goods and document across Indonesia, however to succeed the strategy chosen, both services need cooperation with external partnership. Implementation phase to succeed the strategy using Balanced Scorecard as performance measurement system to an interactive management system for strategy execution, consisting of implementation model, gap analysis between current situation and desire objective, it is also using Balanced Scorecard as performance measurement system as an interactive management system for strategy execution. The objectives on each perspectives create the KPI management and deploy the programs into each functional, at the end to reach positive EVA as financial objective.Keywords: Pasundan Delivery Services, Strategic Management, Balanced Scorecard, KPI, EVA